Effect of Pile Spacing on Group Efficiency in Gypseous Soil - Noman, Bilal Jabbar; Abd-Awn, Safaa H.; Abbas, Hassan O. (Salehan Institute of Higher Education, 2019)
As a matter of fact, the gypseous soil is usually considered as collapsible soil, such type of soil illustrates high resistance to settlement and high bearing capacity when it is dry, but it loses these characteristics when it is inundated and collapses excessively because of the sudden decrease in the volume of the surrounding soil mass. It is founded in the arid and semi-arid regions of the world in Asia, South Asia (Iraq, Syria, Jordan, Yemen, and Iran), North Africa, North America, moreover, it covers more than (31%) of the surface area in Iraq. Gypseous soil is one of the most difficult problems facing the process of building any project because of the difficulty of preventing leakage of water to the soil in practice. Deep foundation (piles) are one of the most common types used in collapsible soils which penetrating problematic soil layers and reaching more hard ones (end bearing piles) or transfers loads depending on skin friction (floating pile). The current work is directed to study the behavior of single and group driven pile of square pattern (4 piles) in case of floating pile (friction pile) with different spacing (2D, 4D, 6D) and length to diameter (L/D) ratio of (20) in this special medium dense soil (gypsum content 30% and 61%) under axial load condition. The investigation was carried out to measure the soil collapse before and after inundation. The results showed that the group efficiency for spacing 2D is less than one while for spacing 4D and 6D are more than that value. In addition, the spacing 4D was more efficient to carry 4 group pile in both dry and soaked cases, in addition, the result showed a high reduction in the bearing capacity at inundation state of group pile of (82% in gypsum content 30%) and ( 87% in gypsum content 61%) with respect to dry state.